The effect of high‐tech services offshoring on skilled employment: intra‐firm evidence (2013)
The offshoring of high‐tech services has greatly increased in recent years, with consequences for firms demand for skilled employment in firms. This paper specifically analyzes the relationship between R&D offshoring and the demand for R&D employment using firm‐level data for Spanish manufacturing and services companies during the period 2004‐2009. Estimating different specifications with panel data techniques, we find that this association is statistically positive. In particular, for services firms a 1 percentage point increase in R&D offshoring raises the demand for researchers by about 11%. This suggests the existence of complementarity among them as productive inputs.